Effect of pre-contraction on β-adrenoceptor-mediated relaxation of rat urinary bladder - Michel, Martin Christian (Springer-Verlag, 2009)
PURPOSE: The human physiological bladder contraction is largely mediated by acetylcholine acting on muscarinic receptors, but in pathophysiological settings the relative role of non-cholinergic stimuli gains importance. β-Adrenoceptor agonists are currently in clinical development as treatments for the overactive bladder syndrome. Therefore, we have explored the ability of the β-adrenoceptor agonist isoprenaline to induce rat isolated bladder strip relaxation on pre-contraction with the muscarinic agonist carbachol as compared to bladder tone induced by several non-cholinergic stimuli. METHODS: Bladder tone was induced by passive tension, receptor independently by KCl, carbachol, bradykinin or serotonin. Concentration–response curves were generated for relaxation by isoprenaline, and a single concentration of the receptor-independent relaxant forskolin was also tested. RESULTS: The various contractile stimuli induced different degrees of bladder tone, but the ability of isoprenaline or forskolin to relax rat bladder was not correlated with the degree of tone. Isoprenaline was significantly less potent and effective in causing relaxation against carbachol-induced tone than against any other stimulus, whereas no such relationship was observed for forskolin. CONCLUSIONS: We conclude that β-adrenoceptor agonists can induce rat bladder relaxation against a wide range of contractile stimuli and are more potent and/or effective against non-cholinergic stimuli than against muscarinic agonism. This profile appears desirable for agents intended for the treatment of overactive bladder.